The Effect of Mole Ratio Natural-CaCO₃/KF in the Synthesis of KCaF₃ Perovskite Base Catalyst - I. F. Nurcahyo; Eddy Heraldy; Suciana Nur Cahyaningsih; Fitria Rahmawati; Khoirina Dwi Nugrahaningtyas; Yuniawan Hidayat; Firanda Larasati (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2024)
The KCaF3 perovskite catalyst was successfully synthesized by reacting limestone (natural-CaCO3) with potassium fluoride (KF). The synthesis of the KCaF3 catalyst was conducted with several variations in the mole ratio of CaCO3 to KF (1:1, 1:2, and 1:3). The research results showed that the addition of KF can affect the characteristics of the catalyst. The optimal catalyst is the KCaF3 catalyst with a mole ratio variation of 1:3. X-ray diffractometer analysis revealed that the highest KCaF3 phase composition reached 74.05%, while thermogravimetric analysis indicated a CaCO3 concentration of 34.50%. Surface Area Analyzer analysis shows that KCaF3 has the largest surface area, which is 187.1 m2/g. This catalyst efficiently facilitated the transesterification of palm oil, yielding 93.4% biodiesel.